Ação de películas de cobre em superfícies manuseáveis sobre carga bacteriana total e acinetobacter spp. em leitos hospitalares - Blehm, Cláudia Justin (2020)
Healthcare-associated infections (HAIs) represent a global challenge and contribute to increasing hospitalization time and costs, morbidity and mortality. Acinetobacter spp., especially A. baumannii, are among the most prevalent agents causing HAIs. Acinetobacter spp. are of particular concern for their ability to form biofilms on abiotic surfaces and to survive for a long time on hospital equipment and surfaces, as well as for their genetic plasticity, which enables to acquire determinants of antimicrobial resistance. In this context, the present study aimed to evaluate copper coating of the high-touch surfaces in the hospital bedrooms with regard to total aerobic bacterial load and presence of Acinetobacter spp., as well as to characterize antimicrobial susceptibility of Acinetobacter baumannii and Acinetobacter nosocomialis. Firstly, we performed an in vitro assay for the evaluation of A. baumannii adhesion and biofilm formation in copper films in comparison with films without copper. We did not detect A. baumannii in copper films by plate counting and scanning electron microscopy. Overall, in the in situ evaluation, copper-coated surfaces presented lower total bacterial load than control. Likewise, Acinetobacter spp. were isolated in more samples from uncoated than copper-coated surfaces, and the majority was identified as A. baumannii. Most A. baumannii isolates were classified as extreme drug-resistant, which were more prevalent on control surfaces. These findings, apparently, indicate that copper coating did not exert co-selection for antibiotic resistance in Acinetobacter spp. A. nosocomialis isolates were susceptible to the majority of the antimicrobials tested. All carbapenem-resistant A. baumannii isolates harbored blaoxa-23 gene, while blaNDM was not detected in any of them. Nevertheless, all A. baumannii and A. nosocomialis isolates were susceptible to polymyxin B. In conclusion, copper coating could be very helpful to compose strategies for sanitizing the hospital environment.